Protecting Outsiders? Corporatism and the dualization of unemployment protection in Germany and Austria - Betthäuser, B (Intersentia, 2017)
Recent research has found that much of the social protection retrenchment since the early 1990s has been targeted at workers with low or instable incomes, resulting in a ‘dualization’ of social protection. However, little is known about the causes for cross-national variation in the way that different welfare states have reformed unemployment protection for these ‘labour market outsiders’. The article sheds light on the potential causes for this variation by considering the cases of Germany and Austria, two countries that have diverged markedly in their reforms of unemployment protection for non-standard workers. Based on a most-similar-systems design and an analysis of the reform trajectories of the two countries, the power of unions to influence the policy process via corporatist institutions and via their ties to political parties is identified as an important factor in this divergence—one that has received surprisingly little attention in the dualization literature thus far.